PROFIL PENDUDUK INDONESIA MENJELANG ERA TINGGAL LANDAS - Ida Bagoes Mantra (Populasi, 1991)
The most important factor of population development during the Second Long-Term Development (PJP 77) is the development of human resources, which is, in  turn, one of the most essential element of development next to natural resources and technology. Before the development of human resources is carried out, the conditions of the human resources themselves should be first detected and indentified.Taking notes of the 1990 population data, it has been concluded that the profile of the population of Indonesia has improved substantially. The population structure of the younger age group has been gradually left behind in accordance with the decline of the population growth rate. Bothbirth and mortality rates have dropped as the result of the significant improvement of the family planning and community - health programs. Spontaneous migration among regions of Indonesia has also increased inaccordance with the development progress,the transport infrastructure, and the populationmobility from rural to urban areas. The value of human quality, even though has experienced some increase, is still considered lowso far.The characteristics of population demography need serioues considerations to be able to improve the efforts to promote the humanwuality of the country.